2002
DOI: 10.1002/bdd.297
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of a novel surface‐active agent, purified poloxamer 188, in rat, rabbit, dog and man

Abstract: Purified poloxamer 188 (PP188) is a non-ionic, block copolymer surfactant that is currently being evaluated clinically in sickle cell disease vaso-occlusive crisis and acute chest syndrome and preclinically in spinal cord injury and muscular dystrophy. This paper describes the pharmacokinetics of PP188 in rats, pregnant rats, pregnant rabbits, dogs and humans. Plasma protein binding interaction studies demonstrated no clinically significant effects on narcotic analgesics, hydroxyurea, warfarin, diazepam or dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
32
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 11 publications
0
32
0
Order By: Relevance
“…In addition, by coating with PEO or PEO-PPO-PEO, a number of studies have demonstrated the Fstealth_ behavior of delivery that decreased the uptake or degradation by the reticuloendothelial system (RES) or reduced the adsorption by plasma proteins (43)(44)(45)(46). Our in vivo pharmacokinetic data (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…In addition, by coating with PEO or PEO-PPO-PEO, a number of studies have demonstrated the Fstealth_ behavior of delivery that decreased the uptake or degradation by the reticuloendothelial system (RES) or reduced the adsorption by plasma proteins (43)(44)(45)(46). Our in vivo pharmacokinetic data (Fig.…”
Section: Discussionmentioning
confidence: 90%
“…Headache, nausea, and back and leg pain have been reported in humans enrolled in pharmacokinetic studies (15,37,38). P188 was used as an emulsifying agent in perfluorocarbon artificial blood, but its use was abandoned because of a high rate of adverse reactions including hypotension, hypoxemia, pulmonary hypertension, and neutropenia (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…P188 has shown promise in the management of many diseases, including sickle cell disease, vascular disease, stroke, and cancer, and clinical trials, involving more than 4,000 patients, have shown it to be safe when administered intravenously. 57 P188 has shown the ability to improve the microcirculation 8 , minimize platelet aggregation 9 , and improve survival after hemorrhagic shock. 10 P188 has also shown the ability to mitigate reperfusion injury after myocardial infarction 11, 12 and improve hemodynamics, and subsequent oxygen delivery, after hemorrhagic shock in humans.…”
Section: Introductionmentioning
confidence: 99%